Navigating rare vascular brain tumors: A retrospective observational study - Sana Ahuja; Dipanker S Mankotia; Naveen Kumar; Vyomika Teckchandani; Sufian Zaheer (Cancer Research, Statistics, and Treatment)
Background: Vascular tumors of the central nervous system (CNS) are rare, requiring precise histopathological evaluation for optimal treatment decisions. Molecular diagnostics, vital for therapy and prognosis, are often unavailable in developing countries. Objectives: This study was primarily aimed to analyze the demographic and clinicopathological features of CNS vascular tumors. The secondary objectives included correlating radiological and histopathological findings and evaluating immunohistochemistry. Materials and Methods: This 3-year (2019-2022) observational study was conducted in the pathology department of a tertiary hospital, Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi, India. Clinical and histopathological features, including immunohistochemistry (IHC), were analyzed. Results: We included 20 cases of vascular tumors, among which there was a male preponderance (male: female = 7:3), with a mean age of 45.6 years (range, 10-75 years). The cerebellum was the most common tumor site (n = 10, 50%). Histologically, hemangioblastoma was the most frequent diagnosis (n = 11, 55%), characterized by clear cytoplasmic stromal cells and positivity for CD34, S100, vimentin, and inhibin on IHC. Other diagnoses included angiomatous meningioma (n = 4, 20%), cavernous hemangioma (n = 3, 15%), and solitary fibrous tumor (n = 2, 10%), each displaying distinct clinical and histopathological profiles. Conclusion: This study emphasizes the rarity of CNS vascular tumors and underscores the pivotal role of accurate histopathological assessment. Despite challenges in molecular diagnostics in resource-limited settings, our findings provide valuable insights into tumor demographics, clinical presentations, and distinct histological characteristics of vascular tumors, fostering a multidisciplinary approach for enhanced diagnostic precision and improved patient outcomes.